Legal Adaptation Of The Crime Of Maritime Piracy And Its Elements From The Perspective Of International Law - Fatima Mohamed Abdulqader Baqais; Norfadhilah Mohamad Ali; Syaryanti Hussin; Hendun Abd. Rahman Shah (Usuli Faqih Research Centre, 2024)
The article deals with the legal conditioning of the crime of maritime piracy and its elements from the perspective of international law, and the article also aims to define the crime of maritime piracy, highlight its seriousness, indicate its legal adaptation, find its pillars a crime and the penalties prescribed for it, and clarify the position of international law on the phenomenon of maritime piracy, analyzing and evaluating the role of international conventions in suppressing piracy. In order to achieve the objectives of the research, the researcher relied on the descriptive analytical approach as it is the best approach in adapting the crime of maritime piracy, stating its elements, and identifying all the elements that distinguish it from the acts that may follow it, and analyzing the topic by shedding light on the position of international law. Among the most important results it was found that the crime of maritime piracy has many definitions, but all of them agree that what distinguishes it is the gravity of the acts that compose it, which prompted its legal criminalization, and that the Geneva Convention on the High Seas of 1958 and the United Nations Convention on the Law of the Sea of ​​1982 did not set an accurate definition of the crime of maritime piracy. It confined itself to mentioning its component acts, and among the most important recommendations was drafting a new international agreement or amending the United Nations Convention on the Law of the Sea to include rules for defining the crime of maritime piracy, approving penalties for its perpetrators, and setting international cooperation rules that oblige all countries, under pain of penalties, to provide what is necessary and what is available to them of Information regarding this crime.